Emocje estetyczne w świetle badań psychologii muzyki: opis i mechanizmy wyjaśniające - Kaleńska-Rodzaj, Julia (Res Facta Nova, 2018)
The main aim of this article is to review contemporary research on aesthetic emotions from the perspective of music psychology. By analyzing the results of research review in the broader theoretical context, the author attempts to answer the question of the appropriateness of distinguishing a separate category of aesthetic emotions and musical aesthetic emotions. She concludes that despite the specific terminology used to describe aesthetic musical emotions (classification of aesthetic emotions by M. Zentner et al.), some specific induction mechanisms (a multi-level theory of emotion causation by P.N. Juslin) and functions fulfilled in the listener’s life, there is no clear evidence to distinguish musical aesthetic emotions as a separate category of emotions, and the term aesthetic emotions should be reserved only for the emotions arising as a result of the cognitive evaluation of the stimulus according the listener’s aesthetic criteria.